Duty to take care of own health: Problems of law content and ensuring legal liability - Anishchenko, M. A.; Hamburh, L. S.; Myrnyi, D. P.; Filei, Y. V.; Tsarov, O. D.; Аніщенко, Михайло Анатолійович; Гамбург, Леонід Самойлович (My University, 2021)
The article examines the legal duty of its citizens to take care of their health established by the laws of Ukraine. The article reveals and substantiates the constitutional-law nature and significance of this duty, its belonging to the sphere of public law in connection with the realization of the general interest in maintaining an adequate level of public health with the simultaneous derivative provision of an individual interest in health protection. The problems of the content of this duty and its provision by society and the state with the help of moral and legal responsibility are investigated: the structure of a legal duty is analyzed, consisting of obligations corresponding to the eligibles of the appropriate subjective right; clarifies the role and significance of moral responsibility (moral duty) and its relationship with legal responsibility.
Keywords: health; health care; taking care of own health; medical examination; vaccination